Discourse revisited: Dimensions and employment of first‐order strategy discourse during institutional adoption - Paroutis, Sotirios; Heracleous, Loizos (Strategic Management Journal, 2013)
Despite decades of research on strategy, we still know little about what the concept of strategy means to actual strategists and how they use it in practice. Working at the intersections of institutional and practice theories, we use exploratory interviews with strategy directors and a longitudinal case study to uncover four dimensions of first‐order strategy discourse: functional, contextual, identity, and metaphorical. We also reveal three phases in the interrelation between first‐order strategy discourse and institutional work: shaping, settling, and selling and a differential emphasis (selective focusing) on dimensions of the first‐order strategy discourse during the institutional adoption process. We contribute to a deeper understanding of the concept of strategy in practice, the process of institutional adoption, and of the role of discourse in this process . Copyright © 2013 John Wiley & Sons, Ltd.